Effect of Recycled Concrete Aggregates, Sisal Fibres, and Carbon Nanofibres on the Mechanical Properties of Concrete - Vatin Nikolai Ivanovich; Mouli Kathi Chandra; Reddy S. Sai Satyanarayana; Dabral Upendra; Mahajan Sulabh; Khurana Sahil; Nancy (E3S Web of Conferences)
This research examines the mechanical properties of concrete by combining recycled concrete aggregates (RCA) with carbon nanofibers and natural sisal fibers, in place of natural aggregates. We created a variety of concrete mixtures with RCA content levels of0%,50%, and 100%, as well as varied fiber combinations. Some mixes included additional cementitious elements such as fly ash (FA) or silica fume (SF). Mechanical tests such as compressive strength, flexural strength, and split tensile strength were used to assess the performance. Findings shown that mechanical properties were significantly enhanced by using sisal and carbon nanofibers. Combine A9, which omitted RCA but included 1% sisal fiber and 0.2% carbon nanofibers, had the highest compressive strength (81.2 MPa), flexural strength (8.84 MPa), and split tensile strength (6.60 MPa). Using 100% RCA replacement (Mix C9) lowered the strength somewhat, however the mix still performed better than regular concrete. Based on the findings, RCA and sustainable fibers may be used into concrete to provide a greener alternative without compromising durability.